2014
DOI: 10.1099/vir.0.068700-0
|View full text |Cite
|
Sign up to set email alerts
|

Novel divergent nidovirus in a python with pneumonia

Abstract: The order Nidovirales contains large, enveloped viruses with a non-segmented positive-stranded RNA genome. Nidoviruses have been detected in man and various animal species, but, to date, there have been no reports of nidovirus in reptiles. In the present study, we describe the detection, characterization, phylogenetic analyses and disease association of a novel divergent nidovirus in the lung of an Indian python (Python molurus) with necrotizing pneumonia. Characterization of the partial genome (>33 000 nt)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
63
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 30 publications
(33 reference statements)
9
63
1
Order By: Relevance
“…New nidoviruses were recently identified in the lungs of cattle and wild shingleback lizards with pneumonia, though their direct association with disease has so far not been examined (31,37). We found MVNV-associated lesions almost exclusively in the airways and lungs, similar to previous reports on nidovirus infections in other python species (8,9,15). The detection of viral RNA by PCR in other tissues, such as the liver, spleen, kidney, and intestine, however, indicated that the viruses spread systemically.…”
Section: Fig 10supporting
confidence: 88%
See 2 more Smart Citations
“…New nidoviruses were recently identified in the lungs of cattle and wild shingleback lizards with pneumonia, though their direct association with disease has so far not been examined (31,37). We found MVNV-associated lesions almost exclusively in the airways and lungs, similar to previous reports on nidovirus infections in other python species (8,9,15). The detection of viral RNA by PCR in other tissues, such as the liver, spleen, kidney, and intestine, however, indicated that the viruses spread systemically.…”
Section: Fig 10supporting
confidence: 88%
“…We also detected viral antigen in epithelial cells of the cranial esophagus in one affected animal; however, in M. viridis the esophagus carries a ciliated epithelium (data not shown), a feature also known for other snake species (57,58); infection could therefore be due to an overspill from the trachea and nasal cavity. We did not detect viral antigen in any cells of the stomach or intestine, and a previous study also did not find viral RNA by RNA-ISH, suggesting that the python nidoviruses are primarily respiratory (8). Viral spread via the expelling of mucus from the nasal cavity would be a likely route of transmission.…”
Section: Fig 10contrasting
confidence: 45%
See 1 more Smart Citation
“…This approach has led to a number of newly detected viruses in various animal species in recent years [3740] and might be of great interest for detecting potentially zoonotic and infectious diseases in wildlife species.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Bafinivirus includes two viruses isolated from fish (White bream virus and White minnow nidovirus) (Batts et al, 2012;Schütze et al, 2006). Within the past year, nidoviruses have been described in pythons with pneumonia [python nidovirus (PNV) and ball python nidovirus (BPNV)] and these viruses are proposed to represent a novel genus within the subfamily Torovirinae (Bodewes et al, 2014;Stenglein et al, 2014;Uccellini et al, 2014). Here, we report on the discovery and genomic characterization of a novel virus that represents a distinctive lineage within this subfamily.…”
mentioning
confidence: 99%